Developing nitrosocarborane chemistry. Issue 8 (26th January 2016) - Powley, Samuel L.; Schaefer, Louise; Man, Wing. Y.; Ellis, David; Rosair, Georgina M.; Welch, Alan J.
Abstract : New nitrosocarboranes or their hydroxylamine or Diels–Alder cycloadducts have been prepared and fully characterised. Abstract : The new nitrosocarboranes [1-NO-2-R-1, 2- closo -C2 B10 H10 ] [R = CH2 Cl (1 ), CH3 OCH2 (2 ) p -MeC6 H4 (3 ), SiMe3 (4 ) and SiMe2 t Bu (5 )] and [1-NO-7-Ph-1, 7- closo -C2 B10 H10 ] (6 ) were synthesised by reaction of the appropriate lithiocarborane in diethyl ether with NOCl in petroleum ether followed by quenching the reaction with aqueous NaHCO3 . These bright-blue compounds were characterised spectroscopically and, in several cases, crystallographically including structural determinations of2 and6 using crystals grown in situ on the diffractometer from liquid samples. In all cases the nitroso group bonds to the carborane as a 1e substituent (bent C–N–O sequence) and has little or no influence on < δ 11 B>, the weighted average 11 B chemical shift, relative to that in the parent (monosubstituted) carborane. Mono- and dinitroso derivatives of 1, 1′-bis( m -carborane), compounds7 and8 respectively, were similarly synthesised but attempts to prepare the mononitroso 1, 1′-bis( o -carborane) by the same protocol led only to the hydroxylamine species [1-(1′-1′, 2′- closo -C2 B10 H11 )-2-N(H)OH-1, 2- closo -C2 B10 H10 ] (9 ); the desired compound [1-(1′-1′, 2′- closo -C2 B10 H11 )-2-NO-1, 2- closo -C2 B10 H10 ] (10 ) was only realised by switching to a non-aqueous work-up. The involvement of water in effecting the net reduction of the NO function in10 to N(H)OH in9 was confirmed by a series of experiments involving [1-N(H)OH-2-Ph-1, 2- closo -C2 B10 H10 ] (11 ), [1-(1′-2′-D-1′, 2′- closo -C2 B10 H10 )-2-D-1, 2- closo -C2 B10 H10 ] (12 ) and [1-(1′-2′-D-1′, 2′- closo -C2 B10 H10 )-2-N(H)OH-1, 2- closo -C2 B10 H10 ] (13 ). It is suggested that during aqueous work-up a water molecule, H-bonded to the acidic C2′H of10, is "delivered" to the adjacent C2NO unit. The ability of the NO group in nitrosocarboranes to undergo Diels–Alder cycloaddition reactions with cyclic 1, 3-dienes was established via the syntheses of [1-(NOC10 H14 )-1, 2- closo -C2 B10 H11 ] (14 ) and [1-(NOC6 H8 )-2-Ph-1, 2- closo -C2 B10 H10 ] (15 ). This strategy was then utilised to prepare derivatives of the elusive dinitroso compounds of [1, 2- closo -C2 B10 H12 ] and 1, 1′-bis( o -carborane) leading to the sterically-crowded products [1, 2-(NOC6 H8 )2 -1, 2- closo -C2 B10 H10 ] (16, prepared as meso and racemic diastereoisomers), [1-{1′-2′-(NOC6 H8 )-1′, 2′- closo -C2 B10 H10 }-2-(NOC6 H8 )-1, 2- closo -C2 B10 H10 ] (17 ) and [1-(1′-1′, 2′- closo -C2 B10 H11 )-2-(NOC6 H8 )-1, 2- closo -C2 B10 H10 ] (18 ).